Aggregated Technical Commercial and Collection Loss Mitigation Through a Smart Metering Application Strategy - Odje, Mathias; Uhunmwangho, Roland; Okedu, Kenneth E. (Frontiers in Energy Research, 2021)
The privatization exercise that led to the creation of 11 distribution companies (Discos) is yet to yield the result of meeting the electricity supply needs of Nigeria. It is in realization of this fact that the Federal Government of Nigeria recently made different proposals and regulations to increase efficiency, availability, and competitiveness within the power industry. This article establishes a technical gain ratio to measure the impact of scaling up smart metering on the aggregated technical commercial and collection (ATC&C) losses. The ATC&C loss is the difference between the amount of electricity received by a distribution company from the transmission company and the amount of electricity for which it invoices its customers plus the adjusted collections loss. To achieve this objective, reviews of historical data of the Discos ATC&C losses and customers’ metering records as published by the Nigerian Electricity Regulatory Commission (NERC) for 2015, 2016, 2017, 2018, and 2020 were carried out. In addition, efforts were made to mathematically model the relationship between % metering and % ATC&C losses as this was the framework to help carry out effective forecasts and analyses of the study in order to show the impact level of the strategy employed. One of the salient technical contributions of this article was that it established that for every 1% increase in metering installation, there is a proportionate 0.8% decrease in ATC&C losses, provided all other factors responsible for technical and commercial losses remain constant. Consequently, improved ATC&C loss reduction would be achieved if Discos adopt a combination of other strategies that would ensure reduction in technical and commercial losses in addition to aggressive deployment of meter assets. However, in practice, factors causing technical and commercial losses are never constant as system components depreciate/burn out with time, energy theft, and pilferage, and meter tamper/bypass is on the increase daily; meter deployment is not aggressive enough to match utility customers’ growth. Hence, the adoption of combined modern strategies in addition to aggressive metering in tandem with customers’ growth has to be employed by Discos in a deliberate attempt to reduce ATC&C losses.